Smart City As A Concept To Redesign City Area, Case Of Lhokseumawe City - Sisca Olivia; Andrian Saiful Adly Nst (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2018)
City is a development from village, and some city problems will show up as an impact of city development, such as congestion and crowded. Many concepts have offered to solve the city problem, like Smart City. This study is to explore smart city concept to redesign city area in Lhokseumawe City. User observation based on their activity and behavior was a method that used in this study, beside of city analysis and field observation. The design ideas were proposed based on the field problem to get better city planning. Several facility ideas and city network were to be as an alternative solution.